1981
DOI: 10.1063/1.441720
|View full text |Cite
|
Sign up to set email alerts
|

Level to level differential cross sections for vibrationally–rotationally inelastic collisions of Na2 with Ar

Abstract: We report measurements of differential cross sections of rotationally (Δj = 15 to 79)–vibrationally (Δv = 1) inelastic collisions in ground electronic state Na2 with Ar on a level to level basis. The experiment is performed using crossed supersonic molecular beams and two dye lasers, one for tagging the initial level (v = 0, ji = 7), and the second for detection of the final level (v = 1, jf = 7+Δj) and scattering angle ϑ. A description of the experimental apparatus and technique is given. The differential cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Previous work (15) indicated that the rotational-state distributions have a very weak dependence on ⌬v; one might reasonably expect to observe larger changes in the DCS, a more sensitive probe of the dynamics, for such large differences in the amount of energy transferred into vibration (recall that the energy of a quantum of D 2 vibration is approximately equal to the height of the reaction barrier on the minimum energy path), but this is not what we observe. Hints of this counterintuitive behavior were also found by Serri et al (24,25) when they measured DCSs for Na 2 ϩ Ar inelastic scattering and found that the peak scattering angle shifted by only 10°b etween ⌬v ϭ 0 and ⌬v ϭ 1 at large ⌬j. The vibrational spacing of Na 2 is small, and its interaction with Ar is almost totally repulsive.…”
Section: Sources Of Errormentioning
confidence: 75%
“…Previous work (15) indicated that the rotational-state distributions have a very weak dependence on ⌬v; one might reasonably expect to observe larger changes in the DCS, a more sensitive probe of the dynamics, for such large differences in the amount of energy transferred into vibration (recall that the energy of a quantum of D 2 vibration is approximately equal to the height of the reaction barrier on the minimum energy path), but this is not what we observe. Hints of this counterintuitive behavior were also found by Serri et al (24,25) when they measured DCSs for Na 2 ϩ Ar inelastic scattering and found that the peak scattering angle shifted by only 10°b etween ⌬v ϭ 0 and ⌬v ϭ 1 at large ⌬j. The vibrational spacing of Na 2 is small, and its interaction with Ar is almost totally repulsive.…”
Section: Sources Of Errormentioning
confidence: 75%
“…Of relevance are the experiments of Kinsey, Pritchard, and coworkers [5,6] who developed laser methods to determine velocity distributions, the velocity selection by Doppler shift method of Smith et al [7,8], and most recently, a fully polarization-resolved, four-vector experiment by Collins, McCaffery, and Wynn [9]. Alternative treat-Coherent 699-29 Coherent Innova 100 PC i Control 3392 LZJ FIG.…”
mentioning
confidence: 99%
“…Gottscho et al [4] extended this to rotationally inelastic collisions of molecules and determined energy averaged, most probable scattering angles for BaO colliding with argon. Of relevance are the experiments of Kinsey, Pritchard, and coworkers [5,6] who developed laser methods to determine velocity distributions, the velocity selection by Doppler shift method of Smith et al [7,8], and most recently, a fully polarization-resolved, four-vector experiment by Collins, McCaffery, and Wynn [9]. Alternative treat- © 1993 The American Physical Society ments of optical-optical double resonance (OODR) line shapes [10,11] do not emphasize the extraction of the scattering angular variables but contribute valuable insights.…”
mentioning
confidence: 99%
“…74 In contrast, the current infrared laser technique offers a substantially more modest angular resolution, currently on the order of ∆(cos θ) ≈ 0.1 and limited by velocity spread in the initial jet. Even for perfectly collimated beams, the Jacobian for velocity-to-frequency space transformation in the current right angle geometry is unfavorable; for a nominally 2 MHz laser bandwidth, the resolution would still be g5°, 58 which is already substantially inferior to the best angular resolution in the time-of-flight experiments. However, since the time-offlight method samples molecules scattered far from the crossing region, the detected flux is low and decreases quadratically with increasing flight path length and energy resolution.…”
Section: Discussionmentioning
confidence: 98%